Os sentidos e significados do sucesso escolar para uma professora de escola pública - Trisotto, Rejane Maria de Almeida (2008)
This research aims to apprehend the senses and meanings of a public school teacher concerning the educational success, understood from the relationship between success and its reverse, the failure. Hence, socio-historical psychology was the theoretical and methodological reference of this work. The studies of Vygotski (1998, 2001, 2002) about the meaning and sense categories were of great importance throughout the researching process. Along with this author, the contributions of Aguiar (1997, 2002, 2005), Ozella (2005), Heller (2000), Bock (2005), Rey Gonzalez (2002, 2003, 2005) and Charlot (2005) served as a major reference for the analysis of the addressed subject. From a qualitative point of view, this study had a public school teacher as a research collaborator with over 25 years of experience in teaching literacy, in which the senses were analyzed according to the meaning core methodology (Aguiar and Ozella, 2005). Inspired by this methodology, interviews mostly with the teacher, and some instruments, such as complementing sentence technique, choice of engraving, writing report of life path, word box and text ideas confrontation were used as procedures for collecting information . In the data analysis, nine meaning cores emerged and ensured access to the senses and meanings of the teacher concerning the educational success. Among the considerations that led this research, it is highlighted four aspects, understood as fundamentals and because they reflect the senses and meanings that the teacher assigns to the educational success / failure. These aspects are: 1) educational success is a condition that results from the student's family life, 2) the student in an educational success condition is docile, obedient and rule follower, 3) the successful student does not need a teacher, 4) success is an effort result. Our senses and meanings are not even known by us or easily accessed mainly because they are complex structures that exist within a historic-cultural movement that incorporates multiple determinations. By knowing teacher senses, we can meet their constitutive mediations and also the process by which was meant their educational success and failure understanding in their school trajectory and thus, produce a potentially important knowledge for all those who want to know better the teacher, contribute to their training qualification